AN ANALYSIS OF MATHEMATICAL COMMUNICATION SKILLS BASED ON SELF-CONFIDENCE AMONG STUDENTS - Musa; Titi Rohaeti; Putik Rustika (EMTEKA: Jurnal Pendidikan Matematika, 2026)
The importance of students' mathematical communication skills and good self-confidence can achieve a good level of communication. However, each student certainly has different self-confidence. The purpose of this study is to analysis mathematical communication skills based on students' self-confidence. This study uses qualitative. The subjects in this study were 6 students of class VII of SMP Negeri 3 Plered, data collection techniques used were self-confidence questionnaires, tests to measure mathematical communication skills, and interviews. The data obtained were then analyzed in 3 stages, namely data reduction, data presentation, and drawing conclusions. The results of the study showed that subjects with high self-confidence had high category mathematical communication skills by meeting 3 indicators of mathematical communication skills, namely stating everyday events into mathematical language or symbols and solving them, connecting real objects, images, and diagrams into mathematical ideas, explaining ideas, situations, and mathematical relations with real objects, images, graphs and algebra. Subjects with moderate self-confidence categories had high and moderate categories of mathematical communication skills. Subjects with a low self-confidence category have high category metamatic communication skills.